Idiosyncratic volatility and stock returns: Indian evidence - Tariq Aziz; Valeed Ahmad Ansari (Cogent Economics & Finance, 2017)
This paper examines the idiosyncratic volatility (IV) puzzle in the Indian stock market for the period 1999-2014. Univariate and bivariate sorting, as well as cross-section regressions, suggest a positive relation between idiosyncratic volatility and future stock returns. However, this relation is sensitive to the choices of portfolio weighting schemes, types of stocks (small, medium, and large), model specifications, and sample periods. Additionally, this study also contests the assumption that the relation between stock returns and predictor variables (including IV) remains same across different points of the conditional distribution and argues that an insignificant relation at the mean level may be significant at the extreme quantiles of the conditional distribution.
Keywords: G12; C21; 330; idiosyncratic volatility; asset pricing; emerging markets; quantile regression